2014
DOI: 10.1007/s12350-014-9980-7
|View full text |Cite
|
Sign up to set email alerts
|

Relation of early post-stress left ventricular dyssynchrony and the extent of angiographic coronary artery disease

Abstract: The patients with multi-vessel CAD had significantly more global and territorial dyssynchrony at early post-stress than at rest. Such quantitative measures of myocardial stunning may assist in the diagnosis of multi-vessel CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 20 publications
1
22
1
2
Order By: Relevance
“…26 Indeed, dyssynchronous contraction in the ischemic region during peak stress, leads to deterioration of LV synchrony as opposed to the normal myocardium that retains its synchrony. 26 As a further validation of their initial findings, Huang et al 18 showed that early post-stress LV mechanical dyssynchrony by phase analysis of gated Tl-201 SPECT MPI is a useful tool to detect multi-vessel CAD.…”
Section: See Related Article Pp 1048-1056mentioning
confidence: 89%
See 3 more Smart Citations
“…26 Indeed, dyssynchronous contraction in the ischemic region during peak stress, leads to deterioration of LV synchrony as opposed to the normal myocardium that retains its synchrony. 26 As a further validation of their initial findings, Huang et al 18 showed that early post-stress LV mechanical dyssynchrony by phase analysis of gated Tl-201 SPECT MPI is a useful tool to detect multi-vessel CAD.…”
Section: See Related Article Pp 1048-1056mentioning
confidence: 89%
“…subsequent coronary angiography were evaluated. 18 There were 57 patients with no CAD, 32 with 1-vessel disease, 36 with 2-vessel disease, and 19 with 3-vessel disease. Patients with multi-vessel CAD had significantly more global and regional LV dyssynchrony at early post-stress imaging as compared to rest.…”
Section: See Related Article Pp 1048-1056mentioning
confidence: 99%
See 2 more Smart Citations
“…3, 4 Aljaroudi 5 outlined other potential clinical applications of LVD including prognostication and risk stratification of patients with ischemic, 6 non-ischemic cardiomyopathy, 7 implantable defibrillators 8 , and end-stage renal disease. 9,10 Several studies have demonstrated the relation of LVD with myocardial ischemic and/or scar burden, [11][12][13] coronary artery disease (CAD) extent 14 , and LV contractile function. 15 However, there are conflicting data in the literature about the effect of different patterns of perfusion abnormality on LVD in CAD patients.…”
mentioning
confidence: 99%